Role of Critical Thinking Skills in Student Social Problem Solving: Peran Keterampilan Berpikir Kritis dalam Pemecahan Masalah Sosial oleh Siswa - Tawfeeq, Mohammed Rafaat Hama (Indonesian Journal of Education Methods Development, 2025)
General Background: Critical thinking has been widely recognized as a fundamental cognitive ability that enhances individuals’ capacity to adapt, evaluate, and make rational decisions in complex social contexts. Specific Background: Within higher education, students often encounter diverse social challenges that require effective problem-solving strategies, yet little research has explicitly examined the link between critical thinking and social problem solving. Knowledge Gap: Despite the acknowledged importance of critical thinking, limited empirical studies have investigated its predictive role in students’ ability to resolve social problems, particularly in non-Western academic contexts. Aims: This study aimed to analyze the relationship between the subscales of critical thinking and the social problem-solving ability of English language students at the University of Halabja. Results: Using a descriptive-correlational design with 179 participants, findings indicated a significant positive correlation between critical thinking components and problem-solving skills, with analysis, assessment, and inductive reasoning emerging as strong predictors, collectively explaining 47% of the variance. Novelty: The study highlights the predictive power of specific critical thinking subskills, offering new insights into how cognitive processes underpin social problem-solving competence. Implications: The findings suggest that integrating critical thinking instruction into higher education curricula may enhance students’ resilience and adaptability in addressing social challenges. Highlight : Critical thinking has a positive correlation with student problem solving ability. Subscales like analysis, assessment, and inductive reasoning are strong predictors. Results highlight the importance of fostering critical thinking in higher education. Keywords : Critical Thinking, Social Problem Solving, English Language Students, Higher Education, Cognitive Skills